The challenge of Persian and Arabic poetry and literature at the court of Jacob Laith and his successors - javad gholamalizadeh; faeze arab yosef abadi (تاریخ ادبیات)
The challenge of Persian and Arabic poetry and literature at the court of Jacob Laith and his successors AbstractAccording to some scholars from the book of the history of Sistan Ya'qub Laith Safari is the revivalist of Persian language and it's not in Arabic and his successors also took Jacob's way have neglected Arabic language and literature. however, the findings of this study prove the contrary and shows the Safari dynasty has not only not been turning away from Arabic, but they have also been loved and loved by it and what about Ya'qub Laith the founder of this dynasty his absence of Arabic comes from baseless. based on this article intends to explain the status of Arabic language and literature at the court of the Safari by descriptive-analytical method, reasons to refuse arabic notion of Ya'qub and his successors and revealing the high rank of Arabic language and literature in the Safari dynasty, the first independent Iranian rule.